ANALISIS PENGEMBANGAN PRASARANA JARINGAN JALAN KOTA SUNGGUMINASA KAITAN DENGAN PENINGKATAN / AKSESIBILITAS PELAYANAN TRANSPORTASI MASYARAKAT - Rosida Maedina Agus (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The study is developed to analyzing the exlent of interaction among areas based on people’s and good movement pattern in order to develop an infrastukture of road network of Sungguminasa town.determining the development to community transportation service as stipulated in the program mamminasata and hinterland region of Makassar metropolitan City. The data were collected by field observation,interviews,and bibliographical review and analysed qualitatively. The study indicates that strong and medium interaction accur in three regions, samata,romangpolong,and paccinongan village. This is due to the short travelling distance and the regions potency which supporte each other.The stepe taken toward road network infrastructure development are to strengthen the role and fuction of the town road network and to estabilish, improve, and exlend new and existing roads which will automatically improve the accessibility of community transportation.